On gravity wave parameterisation in vicinity of low‐level blocking - Markus Geldenhuys (Atmospheric Science Letters, 2022)
Abstract This note is framed as an open question to the community regarding parameterisation schemes using the blocking layer depth to reduce the orographic gravity wave drag. It is the purpose of this note to argue that the current orographic gravity wave drag parameterisation in the vicinity of blocking is inadequate. Reducing the gravity wave amplitude (and thereby reducing the gravity wave drag) by assuming an effective mountain height dependent on the blocking depth is not realistic. The arguments given here will hopefully spark a debate and new considerations, ultimately leading to improvements in current orographic gravity wave drag parameterisations. This note illustrates that low‐level blocking can induce more gravity waves or gravity waves with a higher momentum flux (compared to the current parameterisation schemes). More realistic parameterisation schemes are likely to improve the models' performance. However, the fact is complex theories are needed to describe gravity wave excitation by orography so that it is difficult to represent gravity wave nature by a ‘too simple’ parameterisation scheme.